Simulation-Based Analysis of Energy and Carbon Emissions in the Housing Sector A System Dynamics Approach - Oladokun, Michael Gbolagade; Aigbavboa, Clinton Ohis (Green Energy and Technology, 2018)
XXV, 287 p. 134 illus., 120 illus. in color.